Editorial - Artioli, Giovanna; Foà, Chiara; Sarli, Leopoldo (Acta Biomedica Atenei Parmensis, 2019)
This editorial focuses on qualitative research, often mistakenly considered less scientific than quantitative research, in that it is “research without statistics”. [...]